Assessing The Significance Of The Wifi Score In Determining Clinical Progression And Amputation Risk In Patients With Chronic Limb-Threatening Ischemia And Type 2 Diabetes Mellitus - Winar, Michael Dian; Khosama, Yuansun; Billy Karundeng (Ridwan Institute, 2025)
Chronic Limb Threatening Ischemia (CLTI) represents the most severe stage of peripheral arterial disease, often compounded by comorbid type 2 diabetes mellitus (DMT2), which exacerbates wound healing impairment and increases amputation risk. The Wound, Ischemia, and foot Infection (WIFI) score offers a structured approach to assess limb severity and guide clinical decision-making. Objective: This study aims to evaluate the clinical significance of the WIFI score in predicting disease progression and major amputation risk among CLTI patients with DMT2 Methods: A retrospective cohort analysis was conducted on patients diagnosed with CLTI and DMT2. Clinical outcomes—including mortality and major amputation—were correlated with WIFI staging using Cox regression analysis. Results: Higher initial WIFI scores were significantly associated with increased rates of major amputation (41.7%) and mortality (29.2%) in the high-risk group, compared to 0% in the low-risk group. Patients who underwent angioplasty showed a mean reduction of 2.8 points in WIFI score, correlating with improved outcomes. Cox regression revealed that each 1-point increase in WIFI score was associated with a 1.9-fold increase in amputation risk and a 2.1-fold increase in mortality. Conclusion: The WIFI score is a clinically meaningful tool for predicting outcomes and guiding management in CLTI patients with DMT2. Its integration into routine vascular assessment enhances risk stratification, supports revascularization decisions, and may reduce unnecessary amputations—especially in resource-limited settings.